2006
DOI: 10.1002/jcb.20781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylglyoxal modification and phosphorylation on the chaperone and anti‐apoptotic properties of heat shock protein 27

Abstract: Heat shock protein 27 (Hsp27) is a stress-inducible protein in cells that functions as a molecular chaperone and also as an anti-apoptotic protein. Methylglyoxal (MGO) is a reactive dicarbonyl compound produced from cellular glycolytic intermediates that reacts non-enzymatically with proteins to form products such as argpyrimidine. We found considerable amount of Hsp27 in phosphorylated form (pHsp27) in human cataractous lenses. pHsp27 was the major argpyrimidine-modified protein in brunescent cataractous lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 36 publications
3
68
2
1
Order By: Relevance
“…We have demonstrated in vitro and in vivo that for the e have demonstrated in vitro and in vivo that for the HSP27 caspase-dependent antiapoptotic effect, large nonphosphorylated oligomers of HSP27 were the active form of the protein. 32 Confirming this result, Oya-Ito et al 34 have recently published that the methylglyoxal modification of HSP27, which is reported to favor large oligomers, exacerbates the antiapoptotic caspase-inhibitory properties of HSP27. In contrast, phosphorylated and small oligomers of HSP27 are particulary efficient in binding to F-actin and Daxx 76,85 and it is the phosphorylated form of HSP27 that protects from neurotoxicity.…”
Section: Cytoprotective Function Of Hsp70 and Hsp27mentioning
confidence: 75%
See 1 more Smart Citation
“…We have demonstrated in vitro and in vivo that for the e have demonstrated in vitro and in vivo that for the HSP27 caspase-dependent antiapoptotic effect, large nonphosphorylated oligomers of HSP27 were the active form of the protein. 32 Confirming this result, Oya-Ito et al 34 have recently published that the methylglyoxal modification of HSP27, which is reported to favor large oligomers, exacerbates the antiapoptotic caspase-inhibitory properties of HSP27. In contrast, phosphorylated and small oligomers of HSP27 are particulary efficient in binding to F-actin and Daxx 76,85 and it is the phosphorylated form of HSP27 that protects from neurotoxicity.…”
Section: Cytoprotective Function Of Hsp70 and Hsp27mentioning
confidence: 75%
“…33 MG provokes the formation of large HSP27 oligomers by inducing the formation of Arg-pyrimidine, an MG-arginine adduct. 34 HSP27 and HSP70 interfere with the action of key apoptotic Proteins. The cytoprotective effect of HSP70 and HSP27 is also related to their ability to disable apoptosis.…”
Section: Cytoprotective Function Of Hsp70 and Hsp27mentioning
confidence: 99%
“…HSBP1 was reported to be methylglyoxal modified in endothelial cells exposed to conditions of excessive glucose ). This methylglyoxal modification modulates the oligomeric population of HSPB1, increases its chaperone activity, reduces its interaction with cytochrome c and modulates its anti-apoptotic activity (Oya-Ito et al 2006;Padival et al 2003;Sakamoto et al 2002;van Heijst et al 2006). This can potentially contribute to endothelial dysfunction associated to metabolic syndrome and various cardiovascular diseases, such as atherosclerosis.…”
Section: Posttranslational Modifications Of Shsps and Implications Inmentioning
confidence: 99%
“…77 Confirming these results, it has recently been demonstrated that methylglyoxal modification of HSP27 induces large oligomers formation and increases the anti-apoptotic caspase-inhibitory properties of HSP27. 78 In contrast, for HSP27 interaction with the F-actin and with Daxx, phosphorylated and small oligomers of HSP27 were necessary 73,79 and it is its phosphorylated form that protects against neurotoxicity. 80…”
Section: Hsp27 Hsp70 and Hsp90 Are Anti-apoptotic Proteinsmentioning
confidence: 99%